Teleoperation system using ATM network / A. Nasoruddin Mohamad - Mohamad, A. Nasoruddin (1998)
The solution to today's for safety in industrial processes and plants involves more and more the use of teleoperated devices to avoid human exposure to hazards. Such hazards occurs during operation and maintenance, in normal or accidental conditions, and during decommissioning at the end of the life time of installations. The year 1989 has represented, for teleoperation an important landmark with closure of the first commercial nuclear power stations which have reached the end of their life time. At the same time, a growing concern has generated support for the developments of teleoperation devices which could be used in disordered environmets. For example, these could be Euro - Chernobyl, where routinely employed remote handling equipment could not cope. Progress in the controlled thermonuclear fusion programmes demonstrates the importance of teleoperation in the assembly phase of future reactors as well as in the maintenance and decommissioning phases. The design of fusion reactors is probably the first example to be driven by remote handling concerns.